Courts in conflict : interpreting the layers of justice in post-genocide Rwanda - Palmer, Nicola Frances, 1983- (Oxford (UK); Oxford University Press, 2015)
The rise of international criminal trials has been accompanied by a call for domestic responses to extraordinary violence. Yet there is remarkably limited research on the interactions among local, national, and international transitional justice institutions. Rwanda offers an early example of multilevel courts operating in concert. This book makes a crucial and timely contribution to the examination of these pluralist responses to atrocity at a juncture when holistic approaches are rapidly becoming the policy norm. It focuses on the practices of Rwanda's post-genocide criminal courts.
Towards an interpretive approach to transitional justice -- Interpretation, empirical research, and the role of theory -- Limitations on the research -- Obtaining access and differing opinions -- Ethical research.
Includes bibliographical references and index.
Keywords: Transitional justice -- Rwanda; Gacaca justice system -- Rwanda; Restorative justice -- Rwanda; Genocide -- Rwanda; Postwar reconstruction -- Rwanda; Law -- Criminal Law -- General; Gacaca justice system; Genocide; Postwar reconstruction; Restorative justice; Transitional justice; Rwanda